(untitled) (Journal of the College of Basic Education, 2023)
One of the main topics covered in the educational and psychological research conducted inthe world during the twentieth century, which have important repercussions on education, are the results ofA humanity that must be stopped and invested in it, no matter how much developments have increased in the twenty-first century.And no matter how wide informatics and individual learning systems are..these are researches that were and will remain relevant.With the human being that developments do not cancel out. and research dealing with cognitiveIt is research on (how to store and retrieve information) and has indicated the importance of helping studentsIn developing a coherent body of accessible knowledge.Where psychologists believe that information in our long-term memory is stored in networksinterrelated are called knowledge structures, the size of these structures and the number of connections between the parts of knowledgeAnd the strength of ties and the organization and abundance of relationships, which are all important in processing information and solving problems.